Assessing the impact of probiotics on immunotherapy effectiveness and antibiotic-mediated resistance in cancer: a systematic review and meta-analysis - Zhao, Shuya; Lu, Zian; Zhao, Fangmin; Tang, Shihuan; Zhang, Lishan; Feng, Cuiling (Frontiers in Immunology, 2025)
BackgroundProbiotics have been demonstrated to exert a potential clinical enhancing effect in cancer patients receiving immune checkpoint inhibitors (ICIs), while antibiotics exert a detrimental impact. Prior meta-analysis papers have substantial limitations and are devoid of recent published studies. Therefore, this study aimed to perform an updated meta-analysis and, for the first time, assess whether probiotics can restore the damage of antibiotics to immunotherapy.MethodsA comprehensive literature search was conducted in three English databases and three Chinese databases with a cutoff date of August 11, 2024. The methodological quality of the studies was evaluated using the Newcastle-Ottawa Quality Assessment Scale (NOS) or the Revised Cochrane risk-of-bias tool (RoB 2). Engauge Digitizer v12.1 was employed to extract hazard ratios (HRs) with 95% confidence interval (CI) for survival outcomes when these data were not explicitly provided in the manuscripts. Meta-analysis was conducted using Stata 14 software.ResultsThe study sample comprised eight retrospective and four prospective studies, involving a total of 3,142 participants. The findings indicate that probiotics significantly prolong the overall survival (OS) (I2 = 31.2%; HR=0.58, 95% CI: 0.46-0.73, p < 0.001) and progression-free survival (PFS) (I2 = 65.2%; HR=0.66, 95% CI: 0.54-0.81, p < 0.001) in cancer patients receiving ICIs, enhance the objective response rate (ORR) (I2 = 33.5%; OR=1.75, 95% CI: 1.27-2.40, p = 0.001) and disease control rate (DCR) (I2 = 50.0%; OR=1.93, 95% CI: 1.11-3.35, p = 0.002). For non-small cell lung cancer (NSCLC) patients exposed to antibiotics, the use of probiotics was associated with superior OS (I2 = 0.0%; HR=0.45, 95% CI: 0.34-0.59, p < 0.001) and PFS (I2 = 0.0%; HR=0.48, 95% CI: 0.38-0.62, p < 0.001) when compared to non-users. Subgroup differences were observed regarding the cancer type (P=0.006) and ethnic backgrounds (P=0.011) in OS.ConclusionsThe meta-analysis findings suggest that probiotics can effectively extend the survival of cancer treated with ICIs. In NSCLC, probiotics appear to mitigate the negative impact of antibiotics on immunotherapy effectiveness, which has profound clinical significance. Nevertheless, additional large-scale, high-quality randomized controlled trials are necessary to further validate these findings.Systematic review registrationhttps://www.crd.york.ac.uk/PROSPERO/display_record.php?RecordID=579047, identifier CRD42024579047.